2003
DOI: 10.1152/ajpregu.00153.2003
|View full text |Cite
|
Sign up to set email alerts
|

Serum but not myocardial TNF-α concentration is increased in pacing-induced heart failure in rabbits

Abstract: In animals and patients with severe heart failure (HF), the serum tumor necrosis factor-alpha (TNF-alpha) concentration is increased. It is, however, still controversial whether or not such increased serum TNF-alpha originates from the heart itself or is of peripheral origin secondary to gastrointestinal congestion and increased endotoxin concentration. We therefore now examined TNF-alpha in serum, myocardium, and liver of sham-operated and HF rabbits. In nine rabbits in which HF was induced by left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Furthermore, work from Becker's laboratory (16,29) indicates that TNF-␣ derived from mast cells is the initial source of increased release following ischemia reperfusion. However, multiple cell types and organs may contribute to the increases in serum TNF-␣ characteristic of heart failure, including cardiomyocytes and the liver (1,14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, work from Becker's laboratory (16,29) indicates that TNF-␣ derived from mast cells is the initial source of increased release following ischemia reperfusion. However, multiple cell types and organs may contribute to the increases in serum TNF-␣ characteristic of heart failure, including cardiomyocytes and the liver (1,14,23).…”
Section: Discussionmentioning
confidence: 99%
“…The main data leading to these conclusions are as follows: (1) TNF-␣-induced preconditioning did not phosphorylate the kinases Akt and Erk during reperfusion; (2) specific inhibitors of these kinases did not affect cardioprotection by TNF-␣; (3) TNF-␣ and classic IPC phosphorylated STAT-3 during early reperfusion; and (4) addition of the STAT-3 inhibitor AG 490 abolished the protection afforded by both TNF-␣ and IPC as preconditioning stimuli. During ischemia, 25 in heart failure, 26 or after coronary microembolization, 27 myocardial and/or serum TNF-␣ levels increase and are causally involved in contractile dysfunction. In contrast, in vitro experiments conducted in rats or in mouse hearts have shown that exogenous TNF-␣ could also confer cardioprotection against an I/R insult in a time-and dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Serum was obtained by centrifuging the blood at 8,000 g for 15 min at 4°C. Liver samples and intestinal contents were prepared as described elsewhere (1). Briefly, liver tissues and intestinal contents from ileum, cecum, and colon lumen were weighed, collected in sterile, endotoxin-free tubes, diluted with limulus LAL reagent water (1:10 for liver tissues, 1:1,000 for intestinal contents samples), and homogenized.…”
Section: Animals and Treatmentsmentioning
confidence: 99%